SAT0157 Nephropathy in Henoch-SchÖNlein Purpura: Study of 142 Patients. (23rd January 2014) - Calvo-Río, V.; Loricera, J.; Martín, L.; Ortiz-Sanjuán, F.; Alvarez, L.; González-Vela, M. C.; González-Lamuño, D.; Mata, C.; Gortázar, P.; Rueda-Gotor, J.; Arias, M.; Martínez-Taboada, V.; et al.
Abstract : Background: The prognosis of Henoch-Schönlein Purpura (HSP) is mainly related to renal involvement. Data on nephropathy in HSP are generally the result of analysis of selected populations seen in Nephrology Services. Objectives: In this report we assessed the frequency and outcome of nephritis in a wide and unselected series of HSP patients. Methods: Study of 142 consecutive patients classified as HSP according to the criteria proposed by Michel et al (J Rheumatol 1992; 19:721) since January 1977 to May 2012. All of them had renal involvement. Nephropathy was categorized as mild or severe. Mild nephropathy encompassed those patients with microhematuria (≥ 5 red cell/hpf) and/or proteinuria that did not reach a nephrotic syndrome range. A patient was defined as having severe nephropathy if he/she had: a) nephrotic syndrome (i.e., plasma albumin levels ≤ 25 gr/liter and either 1 gm of proteinuria/day/m 2 of body surface area in children, or > 3.5 gr of proteinuria daily in adults), with or without edema; or b) acute nephritic syndrome (i.e., hematuria with at least 2 of the following abnormalities: hypertension, increased plasma urea or creatinine levels, and oliguria). Renal insufficiency was considered if the plasma creatinine was >125% of the upper limit of normal. Results: We assessed 142 HSP patients with nephritis (HSPN). At disease onset 27.4% of patients had renal involvement. During the clinical course, all of them had palpable purpura. Gastrointestinal (GI) involvement was seen in a 62% of patients. The main GI symptom was the typical colicky abdominal pain. Nausea and/or vomiting were seen in a 17.8% and melena/rectorrhagia in 32.7%. Stool guaiac test was positive in 56.8% of HSPN patients. Joint manifestations (arthralgia and/or arthritis) occurred in 61.3%. However, arthritis was only observed in 38%. Regarding nephritis, most patients had mild nephropathy. Nephrotic syndrome was found in a 12.5%, nephritic syndrome in a 6.8% and renal insufficiency in 25% of the patients. The median (IQR) amount of proteinuria (gr/24 h) was 1 (0.5-2.2) and serum creatinine (mg/dl) was 1.2 (1-2.4). Laboratory data showed leukocytosis in 22.5% and anemia in 12.7%. The mean±SD ESR was 47.1±30.2 mm/1 st hour. Serum IgA levels were increased in 60% (15 of 25 tested) of patients. Corticosteroids were given to 79.6% of HSPN patients and cytotoxic drugs to 19%. After a median (IQR) follow-up of 120.8 (110-132) months complete recovery was observed in 69.7%, persistent, usually mild, hematuria in 14.8% and chronic renal insufficiency in 4.9%. During the acute phase and throughout the complete follow-up dialysis was only required in 2.9% (4/142) of patients but none of them needed kidney transplant. The disease relapsed in 38.6% of HSPN patients. Conclusions: Although renal involvement is the main prognostic factor in patients with HSP, in most cases the renal outcome is benign. Acknowledgements: This study was supported by grants from "Fondo de Investigaciones Sanitarias"PI12/00193 (Spain). This work was also partially supported by RETICS Program, RD08/0075 (RIER) from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None Declared